A Parasitic Array Receiver for ISAR Imaging of Ship Targets Using a Coastal Radar - Fabrizio Santi; Debora Pastina (International Journal of Antennas and Propagation)
The detection and identification of ship targets navigating in coastal areas are essential in order to prevent maritime accidents and to take countermeasures against illegal activities. Usually, coastal radar systems are employed for the detection of vessels, whereas noncooperative ship targets as well as ships not equipped with AIS transponders can be identified by means of dedicated active radar imaging system by means of ISAR processing. In this work, we define a parasitic array receiver for ISAR imaging purposes based on the signal transmitted by an opportunistic coastal radar over its successive scans. In order to obtain the proper cross-range resolution, the physical aperture provided by the array is combined with the synthetic aperture provided by the target motion. By properly designing the array of passive devices, the system is able to correctly observe the signal reflected from the ships over successive scans of the coastal radar. Specifically, the upper bounded interelement spacing provides a correct angular sampling accordingly to the Nyquist theorem and the lower bounded number of elements of the array ensures the continuity of the observation during multiple scans. An ad hoc focusing technique has been then proposed to provide the ISAR images of the ships. Simulated analysis proved the effectiveness of the proposed system to provide top-view images of ship targets suitable for ATR procedures.